Family and Community Medicine residency in Brazil: Brief history - Simas, Keith Bullia da Fonseca (2018)
Introduction: Health in Brazil was established as a universal right from the promulgation of the Constitution of the Federative Republic of Brazil in 1988. Subsequently, ratified and standardized by the edition of the Law 8080 of 1990, which provides the conditions for the promotion, protection and recovery of health, organization and functioning of the corresponding services, known as the organic law of the unique system of Health (SUS). Based on the guiding principles of SUS, the Family Health Program was launched by the Ministry of Health in 1994, which became the Family Health Strategy twelve years later. As the country began to prioritize Primary Health Care (PHC) as the central axis of the health system, as in the main national health systems in the world, the shortage of medical professionals trained to this level of care. The need to expand access to family and community medicine (MFC) in Brazil emerged. Objective: To present aspects of the historical constitution of the Residency Programs in Brazilian CFM (PRMFC). Results: In the first years of the 20th century, in several federal units, there was a considerable increase in RMFC vacancies – with emphasis on the PRMFC of the Municipal Health Department of Rio de Janeiro –, covering cities that did not previously have this training. This context can be understood in the light of the significant articulation built within the SUS, for the formation of human resources in health. Conclusion: The MFC Residency continues to expand in the country and can already be found in some of the main Brazilian cities.